Data distribution in a wireless environment with migrating nodes - Johnston, David A. (2013)
The introduction of mobile wireless devices brings unique challenges for distribution of data to many devices simultaneously. An optimizing multicast methodology called Probabilistic Multicast Trees (PMT) is extended to handle mobile wireless devices. We will show that PMT multiple tree multicast system is well suited to this mobile dynamic environment